2012
DOI: 10.1179/1743284711y.0000000053
|View full text |Cite
|
Sign up to set email alerts
|

On microstructure and properties of Si modified 100Cr6 bearing steels

Abstract: As an alloying element to increase the resistance to softening during tempering, silicon content was modified to investigate its effect on the microstructure and properties of 100Cr6 bearing steel. It turned out that increasing the silicon content brought about two difficulties in the manufacturing process, promoting the decarburisation during heating and/or hot rolling and retarding the spheroidisation of cementite. The maximum size of non-metallic inclusions was predicted to reduce evidently with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…This is attributed to the reduction of γ field caused by adding Si, a ferrite stabilizer. In fact, Kim and Lee [20] have obtained the similar results in N1.0 wt.% Si-modified 100Cr6 bearing steel, but the specific content of Si is not released. According to the above-measured A c1 temperatures and the austenitizing temperature (~840°C) of quenching GCr15 steel, it is thought that the austenitizing temperature of the Si-Moalloyed bearing steels should be higher than 840°C.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…This is attributed to the reduction of γ field caused by adding Si, a ferrite stabilizer. In fact, Kim and Lee [20] have obtained the similar results in N1.0 wt.% Si-modified 100Cr6 bearing steel, but the specific content of Si is not released. According to the above-measured A c1 temperatures and the austenitizing temperature (~840°C) of quenching GCr15 steel, it is thought that the austenitizing temperature of the Si-Moalloyed bearing steels should be higher than 840°C.…”
Section: Methodssupporting
confidence: 66%
“…The chemical composition is listed in Table 1, which was designed by adding~0.36 wt.% Mo and 0.75-1.51 wt.% Si to 1C-1.5Cr bearing steel for enhancing the austenite stability and hindering carbide precipitation during low-temperature austempering to obtain nanostructured bainite. Considering the retarding effect of Si on the carbide spheroidization of steels [20][21][22], the hot rolled bars were spheroidized using 4-cycle annealing, i.e., heating to A c1 + 20°C for 15 min and cooling to A c1 − 50°C for 25 min, repeating 4 cycles, and then furnace cooling to room temperature. The values of A c1 for the three steels were measured on a Netzsch DIL 402C/1/4/G thermal dilatometer by heating to 1000°C at 5°C/min.…”
Section: Methodsmentioning
confidence: 99%
“…7 Nevertheless, the higher stability of retained austenite is, we believe, a more convincing explanation for the improvement of rolling contact fatigue life reported for the Si modified steel. 1 Finally, we would like to emphasise that the fundamental finding of our paper is not that superior rolling contact fatigue characteristics of 100Cr6 steel can be achieved by modifying its composition, but to determine why the retained austenite is more stable in Si modified steel, leading to the improvement of rolling contact fatigue resistance. Daguier et al showed the superior rolling contact fatigue characteristics of 100Cr6 steel in which both Mn and Si contents were increased, but did not address the underlying mechanisms.…”
Section: Kim and Lee Respondmentioning
confidence: 96%
“…The resulting microstructure consists of fine plates of bainitic ferrite separated by carbon-enriched regions of austenite. Kim et al [ 11 ] reported that the Si-modified 100Cr6 bearing steel is 3–4 times superior in terms of rolling contact fatigue (RCF) characteristics compared with the conventional steel when the Si content is increased from 0.25 wt.% to 1.50 wt.%. The excellent RCF performance is attributed to the reduced maximum size of the non-metallic inclusions and the increased stabilization of retained austenite due to the fact that no carbide precipitation occurs during tempering when a higher amount of Si was added to the steel.…”
Section: Introductionmentioning
confidence: 99%